Platelet Surface Charge and Aggregation Effects of Polyelectrolytes - Gröttum, K. A (Thrombosis and Haemostasis, 1969)
The effect on platelet surface charge by adding the polybases : Dextran-DEAE and Polybrene and the polyacids : Dextran sulphate, heparin and bovine platelet fibrinogen to platelet-rich plasma was studied by platelet electrophoresis. In small concentrations all the reagents decreased the electrophoretic mobility of platelets, but not that of erythrocytes, suggesting that the polymeric agents were specifically adsorbed to the platelets and thereby reducing their negative surface charge. When the reagents reduced the electrophoretic mobility of the platelets to 85% of normal, platelet aggregation was induced. This effect was probably not mediated through release of ADP, as the presence of ADPase did not modify the effect. The influence of polybases was not inhibited by EDTA. The effect of Dextran sulphate was inhibited by EDTA and increased by small amounts of calcium ions. Increasing concentrations of Dextran sulphate and heparin increased the electrophoretic mobility of platelets, but did not aggregate the platelets. The results suggest that a decrease in the platelet electrostatic potential is essential in platelet aggregation.